On complexation between methyl cellulose and ammonium nitrate - Majid, Siti Rohana; Arof, Abdul Kariem; Shuhaimi, N.E.A. (Springer Verlag (Germany), 2009)
Films of methyl cellulose (MC) doped with ammonium nitrate (NH(4)NO(3)) salt were prepared by solution casting. From X-ray diffraction, it can be inferred that films of pure MC and MC doped with 5 to 25 wt-% NH(4)NO(3) are amorphous. A small peak at 2 theta similar to 8 degrees indicates that there is interaction between MC and NH(4)NO(3) and a complex has formed. Pure MC has a conductivity of 3.08 x 10(-11) S cm(-1) at room temperature and the conductivity of MC doped with 25 wt-% NH(4)NO(3) is 2.10 x 10(-6) S cm(-1). The increase in conductivity is attributed to the increase in amorphousity and to the increase in number of mobile cations. However, for the sample doped with 30 wt-% NH(4)NO(3), some of the salt has recrystallised out of the polymer host. This is evidenced from the X-ray diffractogram. Recrystallisation of the salt reduces the number of mobile ions for conduction and resulted in a decrease in conductivity. The highest conducting sample was used as an electrolyte in an electric double layer capacitor.